Review of the Effects and Mechanism of Curcumin in the Treatment of Inflammatory Bowel Disease - Lin, Yuan; Liu, Hengjian; Bu, Lingling; Chen, Chen; Ye, Xiaofeng (Frontiers in Pharmacology, 2022)
Curcumin is extracted from the rhizomes of Curcuma longa L. It is now widely used in food processing, cosmetics, dyes, etc. Current researching indicates that curcumin has high medical value, including anti-inflammatory, antioxidant, anti-tumor, anti-apoptotic, anti-fibrosis, immune regulation and other effects, and can be used to treat a variety of diseases. Inflammatory bowel disease (IBD) is a nonspecific inflammatory disease of the intestine including Crohn's disease (CD) and ulcerative colitis (UC). The drug treatment effect is often limited and accompanied by side effects. A large number of basic and clinical studies have shown that curcumin has the effect of treating IBD and also can maintain the remission of IBD. In this review, the research of curcumin on IBD in recent years is summarized in order to provide reference for further research and application of curcumin.